Doping of III-nitride materials. (May 2017) - Pampili, Pietro; Parbrook, Peter J.
Abstract: In this review paper we will report the current state of research regarding the doping of III-nitride materials and their alloys. GaN is a mature material with both n -type and p -type doping relatively well understood, and while n -GaN is easily achieved, p -type doping requires much more care. There are significant efforts to extend the composition range that can be controllably doped for AlGaInN alloys. This would allow application in shorter and longer wavelength optoelectronics as well as extending power electronic devices. It is found that doping of AlGaN and InGaN alloys with low-gallium-content has particular challenges, especially for p -materials and these issues are described.